EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2010)
I would like to direct the attention of the reader to the matter of sustainable progress and development. The first world nations, having started the industrial revolution, have experienced an evolution process longer than the other nations in the globe. Hence, as a rule of thumb, their enterprises have considered a sustainability view. However, the other nations, aiming at their own industrial development and reducing the gap with respect to the more developed countries, normally neglect that aspect, generating a chaotic development of unforeseen consequences, such as India, China, and Brazil itself. A quite illustrative example is the overwhelming global advance of the electronics industry in the past 30 years. Brazilians produce more than 300 tons of electronic residues annually. Unfortunately, the country does not have appropriate places for the disposal of that equipment. The chemical composition of those residues is very diverse. If those plastics and metals are disposed incorrectly in nature, they have the potential to contaminate the soil, the water, and the entire environment. In the first world, there is a established industry for reselling the used electronics that has not been established in Brazil, perhaps due to a cultural issue, then, this turns the country into one of the greatest generators of electronic residues in the world. The used electronic boards are sold as scrap metals and plastics at a low price to Europe for reprocessing and the rest is simply buried, since they contain brome based plastics that are not suitable for recycling with currently available technologies. There are several possible routes for searching a solution to the problem, such as mechanical, chemical, and energetic plastics recycling, and for the metals pyrometallurgy, hydrometallurgy, mechanical processing and electrometallurgy. However, all such routes require scientific research and development in which certainly the area of thermal engineering is a major component.